Characteristics and land suitability of newly establish rice field in Lesung Batu Muda, Rawas Ulu, Musi Rawas, South Sumatera - R Sudaryanto; S Supriyadi; D Mufid (Journal of Degraded and Mining Lands Management, 2015)
Rice field has a strategic function because it is the main provider of food for the population of Indonesia. The data of the land use for the rice field in Indonesia showed that around 41% in Java Island. Agricultural technology at the level of industry experienced rapid progress, but the technology implementation at the level by farmer is relatively slow. Increased production of rice in Indonesia was reported of less than 1% per year. The research aimed to study the characteristics and land suitability of newly established rice field in Lesung Batu Muda, Rawas Ulu, Musi Rawas, South Sumatera. There were two soil land units that were tested included water availability, rooting medium, level of erosion, soil chemical properties and land preparation. The results of the study showed that newly established rice fields in Lesung Batu Muda, Rawas Ulu, Musi Rawas, South Sumatera could be used to open new rice fields by planting twice a year. In opening new rice fields, the application of organic matter and creation of terracing on sloping areas were needed.